Endovascular GDC Treatment of an Idiopathic Carotid-Cavernous Fistula Caused by Aneurysmal Rupture of the Intra-Cavernous Carotid Artery: Case Report - Tatewaki, Y. (Centauro S.r.l., 2006)
Aneurysmal rupture of the intra-cavernous carotid artery may cause idiopathic carotid-cavernous fistula (CCF), and the treatment choice for occluding shunting fistula in this type of CCF is an endovascular approach using detachable balloons. However, little has been reported on treating such lesions with the intra-aneurysmal embolization using Guglielmi detachable coils (GDCs). To our knowledge, ours is the first reported case of successful treatment by selective intra-fistula and intra-aneurysmal embolization with GDCs. A 74-year-old woman exhibited proptosis and chemosis of her left eye over a period of one month. Symptoms of double vision in conversion and pulsatile murmur in her left eye were also noted. Angiography revealed an intra-cavernous aneurysm of the left internal carotid artery (ICA) with a shunting fistula, which drained into the dilated cavernous sinus, superior orbital vein (SOV), superior petrosal sinus, inferior petrosal sinus, and pterygoid plexus. We thought the fistula would occlude by intra-aneurysmal embolization, but we had no confidence of tight packing of the aneurysm since the aneurismal neck was relatively wide. So, we embolized the venous side of the shunting fistula and then the dome of the aneurysm with GDCs. Immediately after the operation, her symptoms and signs were ameliorated, and complete occlusion of the CCF was observed on long-term follow-up. We suggest selective intrafistula and intra-aneurysmal embolization with GDCs as an alternative method of treatment of idiopathic CCF originating from aneurysmal rupture of the intra-cavernous carotid artery.